TESTING THE EFFECTIVENESS OF INTEGRATED ELDERLY CARE MODEL ON QUALITY OF CARE AND HEALTH OUTCOMES AMONG HOSPITALIZED ELDERLIES IN WEST BANK - Atef H. Khatib; Ayman M. Hamdan- Mansour; Hamza F. Ratrout; Atallah Alenezi; Tala R. Chahien (Malaysian Journal of Public Health Medicine, 2020)
The rapid increase in the ageing population and health conditions are imposing a higher challenge to the health care system that requires multidisciplinary teamwork utilizing coordinated care approach. This study examined the effects of integrated care model on quality of care received by older hospitalized patients in West Bank. A quantitative interrupted time series design (pretest and posttest multiple time series, quasi-experiment design) was used. The study examined the effects of integrated care model on admitted older patients (n=32) in the West Bank measuring ten dimensions of quality of care and four health indicators. There was a significant improvement in the dimensions of quality of care: dimensions: nurses’ communications with patients, physicians’ communications with patients, staff response to patients’ needs, pain management, explanations on medications, amount of information given on discharge plan, patients' area cleanliness, patients' area quietness, rating of the hospital, and willingness to recommend the hospital. Incidence of falls and incidence of pressure ulcer improved after implementing the model, while readmission rate and average length of stay did not improve. This study contributed to the limited body of knowledge related to the effect of integrated care model on hospitalized older patients’ quality of care in Palestine/ West Bank. Integrated care has the potential to improve care outcomes among hospitalized older patients.